A Pregnancy with Severe Hypertrophic Obstructive Cardiomyopathy after Surgery for an Implantable Cardioverter Defibrillator: A Case Report and Literature Review. (18th October 2016) - Mitsui, Takashi; Masuyama, Hisashi; Ejiri, Kentaro; Hayata, Kei; Ito, Hiroshi; Hiramatsu, Yuji
Abstract : Hypertrophic obstructive cardiomyopathy (HOCM) is cardiac hypertrophy of ventricular myocardium with left ventricular outflow tract obstruction. We report a pregnancy with HOCM after defibrillator implantation surgery. The patient was a 33-year-old nulligravida and was categorized as New York Heart Association class II. Her brain natriuretic peptide (BNP) level was 724.6 pg/dL at preconception. She received careful pregnancy management. However, because frequent uterine contractions were observed at 25 weeks and 6 days of pregnancy, she was hospitalized, and magnesium sulfate was started as a tocolytic agent. At 27 weeks and 5 days of pregnancy, she had respiratory discomfort and orthopnea with a sudden decrease in peripheral oxygen saturation. Cardiac ultrasonography showed a worsened condition of HOCM and her BNP level was 1418.0 pg/mL. We performed an emergent cesarean section and she delivered a boy weighing 999 g. The Apgar score was 8 and 9 points at 1 and 5 minutes, respectively. The mother's heart failure quickly improved after birth and she was discharged at 10 days postoperatively. Fluctuations in circulatory dynamics during pregnancy may sometimes exacerbate heart disease. Therefore, the risks should be fully explained and careful assessment of cardiac function should be performed during pregnancy in patients with severe HOCM.